Mechanisms of muscular electrophysiological and mitochondrial dysfunction following exposure to malathion, an organophosphorus pesticide. (March 2014) - Karami-Mohajeri, S; Hadian, MR; Fouladdel, S; Azizi, E; Ghahramani, MH; Hosseini, R; Abdollahi, M
Muscle dysfunction in acute organophosphorus (OP) poisoning is a cause of death in human. The present study was conducted to identify the mechanism of action of OP in terms of muscle mitochondrial dysfunction. Electromyography (EMG) was conducted on rats exposed to the acute oral dose of malathion (400 mg/kg) that could inhibit acetylcholinesterase activity up to 70%. The function of mitochondrial respiratory chain and the rate of production of reactive oxygen species (ROS) from intact mitochondria were measured. The bioenergetic pathways were studied by measurement of adenosine triphosphate (ATP), lactate, and glycogen. To identify mitochondrial-dependent apoptotic pathways, the messenger RNA (mRNA) expression of bax and bcl-2, protein expression of caspase-9, mitochondrial cytochrome c release, and DNA damage were measured. The EMG confirmed muscle weakness. The reduction in activity of mitochondrial complexes and muscular glycogen with an elevation of lactate was in association with impairment of cellular respiration. The reduction in mitochondrial proapoptotic stimuli is indicative of autophagic process inducing cytoprotective effects in the early stage of stress. Downregulation of apoptotic signaling may be due to reduction in ATP and ROS, and genotoxic potential of malathion. The maintenance of mitochondrial integrity by means of artificial electron donors and increasing exogenous ATP might prevent toxicity of OPs.